2018
DOI: 10.1152/jn.00490.2018
|View full text |Cite
|
Sign up to set email alerts
|

The influence of input excitation on the inter- and intra-day reliability of the motor unit firing rate versus recruitment threshold relationship

Abstract: Decomposition of the surface electromyographic (sEMG) signal is commonly used to examine motor unit (MU) firing behavior. However, the intra- and inter-day reliability of these measurements has yet to be quantified or reported. This investigation 1) examined the effect of input excitation on the mean firing rate (MFR) vs. recruitment threshold (RT) relationship and 2) determined the inter- and intra-day reliability of the MFR vs. RT relationship at 30%, 50%, and 70% of maximum voluntary isometric strength (MVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…The slope of the regression from EMG variables and joint torque was then correlated with the slope of the regression lines between MU variables and RTs. Furthermore, all subjects and contraction intensities were collapsed and analyzed, rather than assessing by individual subjects and contraction intensities Decomposition is a common technique to analyze EMG from the surface of the skin to determine MU behavior (Beck et al 2011;Colquhoun et al 2018b;Dimmick et al 2018;Enoka 2019; . Recently, Colquhoun et al (2018b) quantified intra and inter-day reliability of the slopes and y-intercepts of the Delsys PDIII decomposition algorithm (PDIII) and found ICC's between 0.766-0.919 for the slopes and 0.780-0.927 for the y-intercepts.…”
Section: Firing Rate Behavior and Amplitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…The slope of the regression from EMG variables and joint torque was then correlated with the slope of the regression lines between MU variables and RTs. Furthermore, all subjects and contraction intensities were collapsed and analyzed, rather than assessing by individual subjects and contraction intensities Decomposition is a common technique to analyze EMG from the surface of the skin to determine MU behavior (Beck et al 2011;Colquhoun et al 2018b;Dimmick et al 2018;Enoka 2019; . Recently, Colquhoun et al (2018b) quantified intra and inter-day reliability of the slopes and y-intercepts of the Delsys PDIII decomposition algorithm (PDIII) and found ICC's between 0.766-0.919 for the slopes and 0.780-0.927 for the y-intercepts.…”
Section: Firing Rate Behavior and Amplitudesmentioning
confidence: 99%
“…Furthermore, all subjects and contraction intensities were collapsed and analyzed, rather than assessing by individual subjects and contraction intensities Decomposition is a common technique to analyze EMG from the surface of the skin to determine MU behavior (Beck et al 2011;Colquhoun et al 2018b;Dimmick et al 2018;Enoka 2019; . Recently, Colquhoun et al (2018b) quantified intra and inter-day reliability of the slopes and y-intercepts of the Delsys PDIII decomposition algorithm (PDIII) and found ICC's between 0.766-0.919 for the slopes and 0.780-0.927 for the y-intercepts. These findings provide information for the PDIII system as a reliable method for assessing changes in firing rate behavior and excitation to the motorneuron pool during an isometric contraction at differing intensities (Colquhoun et al 2018b).…”
Section: Firing Rate Behavior and Amplitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…The four channels of EMG recorded during each ramped contraction were decomposed into their constituent MUAPTs using the Precision Decomposition III (PD III) method (Delsys). This method has been previously described in detail (De Luca et al 2006;Kline and De Luca 2014;Nawab et al 2010), independently two-source validated against intramuscular EMG assessment during low levels of isometric force contractions (Hu et al 2014), and shown to have good intra-and interday reliability (Colquhoun et al 2018). In the current study, validation of MUAPTs was performed in accordance with De Luca and Contessa (2012), where each identified MUAPT was compared with a synthesized sum of MUAPTs with additional Gaussian noise and a root mean square (RMS) value equal to the original signal.…”
Section: Ethical Approvalmentioning
confidence: 99%
“…Additionally, there are two kinds of motor unit physiology: a smaller motor unit, which is slow-twitching, a type I muscle fiber, and fatigue-resisted, and a larger motor unit, which is fast-twitching and has type II muscle fiber fatigability [41]. In addition, during an isometric contraction, there is a negative correlation between the recruitment threshold and the mean firing rate; a higher RT has been found to respond to a lower MFR [28,42,43]. One study found that a type I motor unit's MFR was higher than that of type II.…”
Section: Discussionmentioning
confidence: 99%